Towards self-access CALL: what students say. - Liew , Nyuk Lan; Lee, Geok Imm; Chan, Mei Yuit (Srinakharinwirot University & Thailand Cyber University & Commission on Higher Education Thailand, 2008)
The success of CALL (computer-assisted language learning) self-access centres depend largely on students’ receptivity towards the use of CALL in their learning,as well as their motivation to use the facilities offered. Lack of exposure to self-access learning and computer skills required for CALL also contribute to under-utilisation of CALL self-access facilities. In UPM, in line with the direction the university is taking to encourage more student-centred learning to complement classroom teaching, a pilot CALL programme involving the participation of 1800 students was implemented as a platform to provide initial exposure to the CALL self-access mode of learning. At the end of the programme, a survey was carried out to evaluate the extent of students’ receptivity to the CALL self-access mode of learning, their acceptance of the courseware used, their preference for the types of activities, and feedback on the implementation aspects of the programme. This paper presents the survey results obtained from the project that represent feedback on the programme from the students. Students’ perception of the programme provides valuable information on how well the programme is received and how ready the students are to the practice of self-access CALL. The results of this survey will inform the university’s effort towards the implementation of full-fledged self-access CALL programmes.